The Relationship between Illness of Acceptance and Health Literacy with Type 2 Diabetes - Hanife Efsane Demiröz; Tuğçe Türten Kaymaz (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: To adopt healthy lifestyles for managing chronic diseases and ensure self-management and control of illness, individuals must accept their illness and have good health literacy knowledge. Aim: The study aimed to investigate the correlation between health literacy and illness acceptance in patients with Type 2 diabetes. Method: The study was carried out as a cross-sectional study in Türkiye between December 2019 and April 2020. The sample consisted of 406 participants diagnosed with Type 2 diabetes admitted to a public hospital. Data was collected with the Information Form, the Acceptance of Illness Scale, and the European Health Literacy Survey. Descriptive statistical methods, regression, and correlation tests were employed for analysis. Results: Participants had a mean the Acceptance of Illness Scale score of 26.21 ± 7.11. The participants had a mean the European Health Literacy Survey score of 92.25 ± 15.76. Health literacy, age, gender, people living together, smoking status, hospitalization, knowing about chronic complications, the presence of other chronic illnesses, foot care, and blood glucose monitoring were predictors of the acceptance of illness. A positive correlation was observed between the Acceptance of Illness Scale and the European Health Literacy Survey (r = 0.46; p lt; 0.001). Conclusion: Participants demonstrated high levels of both Health literacy and illness acceptance. The level of illness acceptance increased with the level of Health literacy. It is necessary to develop educational content and materials tailored to the needs and Health literacy levels of the patients to enhance their health literacy.